High-performance soft composite material and preparation method thereof
By chemically treating bamboo and composite elastic film, the problem of easy cracking and unsatisfactory softening effect of bamboo is solved, and the preparation of high-performance softened composite materials is realized, which improves the tensile strength, fold resistance and flexibility of bamboo, and is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411991963.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The longitudinal arrangement of bamboo fibroblasts leads to their lateral cracking, and the vertical and horizontal flexibility varies greatly, which limits their application in the fields of special-shaped decoration, flexible packaging, etc. The softening effect of the existing technology is not ideal, the tensile strength is low, and the composite material technology fails to fully utilize the advantages of bamboo and plastic films.
A softened composite material is used, which includes a biomass material matrix obtained by chemical treatment and an elastic film present on the surface of the substrate, at least part of the elastic film penetrates into the gaps and pores of the substrate, and forms a film-like protective layer on the surface of the substrate.
It realizes high-performance softening of bamboo, improves tensile strength, fold resistance and flexibility, so that it can replace plastics and wood for application in special-shaped decoration, flexible packaging and other fields, and is suitable for mass production.
Smart Images

Figure CN119820945A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-performance flexible composite material and a preparation method thereof, and belongs to the field of biomass material application. Background Art
[0002] With the increasing awareness of environmental protection, finding renewable and degradable materials to replace traditional plastic materials has become a research hotspot. Bamboo, as a plant with abundant resources, high strength, good toughness and renewable nature, has excellent mechanical properties and environmental protection characteristics, and is an ideal alternative material. Bamboo has been widely used in construction, furniture, interior decoration and other fields.
[0003] However, the longitudinal arrangement of bamboo fiber cells makes it easy to crack in the transverse direction, and the flexibility difference between the longitudinal and transverse directions is large, which limits its application in special-shaped decoration and flexible packaging. In the prior art, most of the thin bamboo sliced by bamboo squares rely on reducing the thickness or compounding plastic films to increase the flexibility of the thin bamboo, but there are problems such as poor softening effect and low tensile strength. The single film coating treatment fails to fundamentally solve the problem of easy breakage of bamboo. Therefore, it is of great significance to develop an efficient bamboo softening treatment and preparation method of its composite material.
[0004] In addition, bamboo itself has excellent longitudinal flexibility, but it is easy to crack in the transverse direction and has low tensile strength. The common method to improve bamboo skin is to immediately fix it with non-woven fabric after planing, which can improve its cracking behavior. However, since non-woven fabric affects the aesthetics of the bamboo surface, and its opacity blocks the unique texture of bamboo, it can only be used as a backing material. Bamboo skin without non-woven fabric is still difficult to overcome the cracking problem.
[0005] The longitudinal orderly arrangement of bamboo fiber cells makes it easy to crack in the transverse direction. This structural feature makes bamboo easy to crack along the fiber direction when subjected to force, limiting its use in applications that require transverse strength. In addition, bamboo has higher longitudinal strength and better flexibility, while its transverse strength is low and its flexibility is poor. This difference in longitudinal and transverse flexibility greatly limits its application in special-shaped decoration, flexible packaging and handicrafts.
[0006] In the prior art, the method of increasing the flexibility of bamboo by reducing the thickness of thin bamboo or compounding plastic film can prevent the bamboo fiber from cracking in the horizontal direction to a certain extent, but the softening effect is not ideal and cannot fundamentally solve the problem of easy breakage of bamboo. In addition, the use of plastic film also has the problem of environmental pollution. However, the single coating treatment method only bonds the plastic film to the surface of bamboo. When subjected to external stress, the film is easy to debond from the surface of bamboo, making the material still easy to break under stress, and cannot significantly improve the mechanical strength of bamboo, affecting its application range and reliability.
[0007] The reasons for the above problems are mainly as follows: the structural limitations of bamboo, the natural arrangement of bamboo fibers leads to its inherent deficiencies in flexibility and strength, especially in lateral strength and flexibility. The existing treatment methods are single, and the existing treatment methods are mainly focused on the physical level. Through simple thickness reduction or coating treatment, the structural characteristics of bamboo cannot be fundamentally changed, resulting in limited softening effect. Composite materials have technical deficiencies. The existing composite material technology fails to fully utilize the advantages of plastic film and bamboo, and fails to significantly improve the comprehensive performance of bamboo. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In view of the technical problems existing in the prior art, such as easy lateral cracking and unsatisfactory softening effect, the present invention first provides a high-performance softening composite material. The softening composite material of the present invention is a composite material with excellent tensile strength, folding resistance and flexibility, so that it can replace plastic and wood and be applied to the fields of special-shaped decoration, flexible packaging and handicrafts.
[0010] Furthermore, the present invention also provides a method for preparing a softened composite material. The method is simple and easy to implement, and the raw materials are easy to obtain, so the method is suitable for mass production.
[0011] Solutions for solving problems
[0012] The present invention provides a softening composite material, comprising:
[0013] a substrate, the substrate being derived from a biomass material; and
[0014] an elastic film, the elastic film being present on at least one surface of the substrate; and
[0015] At least a portion of the elastic film penetrates into the gaps and / or pores of the substrate.
[0016] According to the softened composite material of the present invention, the matrix is obtained by chemically treating the biomass material;
[0017] Preferably, the biomass material comprises wood material or bamboo material; and / or,
[0018] The thickness of the biomass material is 0.1-1 mm, preferably 0.15-0.25 mm.
[0019] According to the flexible composite material of the present invention, the material of the elastic film comprises ethylene-vinyl acetate copolymer; and / or,
[0020] The thickness of the elastic film is 0.1-1.5 mm.
[0021] According to the softening composite material of the present invention, the elastic film is present on one surface of the substrate, and an elastomeric material is also contained on the side of the substrate opposite to the elastic film; wherein,
[0022] The elastomeric material forms a film-like protective layer on the side of the substrate opposite to the elastic film; and
[0023] at least a portion of the elastomeric material penetrates into the interstices and / or pores of the substrate;
[0024] Preferably, the elastomeric material comprises waterborne polyurethane.
[0025] The present invention also provides a method for preparing the softened composite material according to the present invention, wherein the preparation method comprises the steps of composite-molding an elastic film and a substrate, and allowing at least a portion of the elastic film to penetrate into the gaps and / or pores of the substrate.
[0026] According to the preparation method of the present invention, the preparation method of the softened composite material comprises the following steps:
[0027] Chemically treating the biomass material with alkaline substances and / or oxides to obtain a matrix;
[0028] Laying an elastic film on at least one surface of the substrate to obtain a formed body;
[0029] The molded body is subjected to a pressurized curing treatment to obtain a softened composite material.
[0030] According to the preparation method of the present invention, the preparation method comprises the following steps:
[0031] Using the alkaline substance and / or the oxide to chemically treat the biomass material to obtain a matrix;
[0032] Laying the elastic film on one surface of the substrate to obtain a first formed body;
[0033] Applying an elastomer solution on the side of the substrate opposite to the elastic film, so that the elastomer material forms a film-like protective layer on the surface of the substrate to obtain a second molded body;
[0034] The second molded body is subjected to a pressurized curing process to obtain a softened composite material.
[0035] According to the preparation method of the present invention, the alkaline substance includes one or a combination of two or more of KOH, NaOH, Na2SO3, K2SO3, Na2CO3, K2CO3; the oxide includes one or a combination of two or more of H2O2, NaClO2, NaClO;
[0036] Preferably, the chemical treatment time is 1s-120h.
[0037] According to the preparation method of the present invention, the solid content of the elastomer solution is 28-34%; and / or,
[0038] The elastomer solution is applied to the side of the substrate opposite to the elastic film by one or a combination of two or more of laying, coating, casting and spraying to form a film-like protective layer.
[0039] According to the preparation method of the present invention, the temperature of the pressurized curing is 60-90° C., the time of the pressurized curing is 5-10 minutes, and the pressure of the pressurized curing is 1-4 MPa.
[0040] Effects of the Invention
[0041] The softened composite material of the invention has excellent tensile strength, folding resistance and flexibility, and can replace plastics and wood and be applied to the fields of special-shaped decoration, flexible packaging and handicrafts.
[0042] Furthermore, the preparation method of the softened composite material of the present invention is simple and easy, the raw materials are easy to obtain, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The surface morphologies, locally enlarged surface morphologies, and cross-sectional morphologies of the softened composite materials of Examples 1 to 3 of the present invention and the traditional composite material of Comparative Example 1 are shown. DETAILED DESCRIPTION
[0044] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0045] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0046] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0047] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0048] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0049] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.
[0050] <First aspect>
[0051] A first aspect of the present invention provides a flexible composite material comprising:
[0052] a substrate, the substrate being derived from a biomass material; and
[0053] an elastic film, the elastic film being present on at least one surface of the substrate; and
[0054] At least a portion of the elastic film penetrates into the gaps and / or pores of the substrate.
[0055] The softened composite material of the invention has excellent tensile strength, folding resistance and flexibility, and can replace plastics and wood and be applied to the fields of special-shaped decoration, flexible packaging and handicrafts.
[0056] Matrix
[0057] The matrix is derived from biomass material, and the matrix is obtained by chemically treating the biomass material. Specifically, in the present invention, the biomass material is derived from wood material or bamboo material, and preferably, the biomass material is derived from bamboo skin (thin bamboo) or wood skin (thin wood).
[0058] Bamboo veneer includes common natural and carbonized side-pressed sliced bamboo veneer, rotary cut bamboo veneer, sliced reconstructed bamboo veneer, flat-pressed sliced bamboo veneer or other bamboo veneer prepared from bamboo integrated materials as sliced raw materials. The rotary cut bamboo veneer is a bamboo veneer material prepared from bamboo as raw material through rotary cutting technology. The sliced reconstructed bamboo veneer is a reconstructed bamboo veneer material prepared from reconstructed bamboo as raw material through softening sliced technology. The wood veneer may include sliced reconstructed veneer, sliced veneer or rotary cut veneer. The sliced reconstructed veneer is a reconstructed veneer material prepared from reconstructed wood as raw material through softening sliced technology. The sliced veneer is a veneer material prepared from the wood part obtained from trees through softening sliced technology. The rotary cut veneer is a veneer material prepared from rotary cutting technology.
[0059] In some specific embodiments, the thickness of the substrate is 0.1-1 mm, preferably 0.15-0.25 mm, for example: 0.12 mm, 0.16 mm, 0.18 mm, 0.2 mm, 0.22 mm, 0.24 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.8 mm, etc.
[0060] In addition, at least one side of the substrate of the present invention also has a backing layer, so as to further fix and support the substrate. Specifically, the backing layer can be a non-woven fabric.
[0061] In some specific embodiments, the matrix is obtained by chemically treating the biomass material. The inventors of the present invention have found that chemical treatment can remove the hard lignin components in the cell corners of the matrix, so that the longitudinally arranged fiber cells are separated, macro cracks are generated, and a large number of micro-nano pores are formed in the cell wall.
[0062] Specifically, the chemical treatment of the present invention includes chemically treating the biomass material with alkaline substances and / or oxides. Chemically treating the biomass material with alkaline substances can further promote mercerization of cell wall skeleton substances, thereby reducing the hardness and rigidity of the bamboo material itself.
[0063] Elastic film
[0064] The inventors of the present invention have found that by laying an elastic film, the gaps and pore structures of the biomass material can be filled and wrapped in multiple scales, thereby improving the flexibility of the biomass material. In the process of compounding the elastic film with the biomass material, the elastic film forms a protective film on the surface of the thin bamboo, and on the other hand, it can flow into the multi-scale gaps and / or pores of the substrate under the action of high temperature, thereby improving the flexibility of the substrate. The softened composite material with the elastic film laid has excellent tensile strength and folding resistance.
[0065] In some specific embodiments, the elastic film can be an ethylene-vinyl acetate copolymer (EVA) film. Specifically, the thickness of the elastic film is 0.05-0.6 mm, such as 0.1 mm, 0.12 mm, 0.16 mm, 0.18 mm, 0.2 mm, 0.22 mm, 0.24 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm.
[0066] In some specific embodiments, when one surface of the substrate has a backing layer, the elastic film can be laid on the side having the backing layer.
[0067] Elastomer materials
[0068] The inventors of the present invention have found that elastomeric materials with good compatibility and elasticity can further fill and wrap the gaps and pore structures of biomass materials in a multi-scale manner, thereby improving the flexibility of the biomass materials.
[0069] In some specific embodiments, the elastic film is present on one surface of the substrate, and an elastomeric material is also present on a side of the substrate opposite to the elastic film; wherein the elastomeric material forms a film-like protective layer on the surface of the substrate; and at least a portion of the elastomeric material penetrates into the gaps and / or pores of the substrate. By allowing the elastomeric material to penetrate into the pores of the substrate, the flexibility of the bamboo material can be fully increased.
[0070] Specifically, in the present invention, the elastomeric material includes but is not limited to elastomeric resin materials such as waterborne polyurethane, etc. The elastomeric material is preferably waterborne polyurethane.
[0071] In some specific embodiments, the pores of the backing layer may also be infiltrated with an elastomeric material. By infiltrating the pores of the backing layer with an elastomeric material, the stress dispersion of the flexible composite material can be further improved.
[0072] <Second Aspect>
[0073] The second aspect of the present invention provides a softened composite material according to the first aspect of the present invention, wherein the preparation method comprises the steps of compositely molding an elastic film and a substrate, and allowing at least a portion of the elastic film to penetrate into the gaps and / or pores of the substrate.
[0074] The preparation method of the softening composite material of the present invention is simple and easy to implement, the raw materials are easy to obtain, and it is suitable for mass production.
[0075] In some specific embodiments, the method for preparing the softened composite material comprises the following steps:
[0076] Chemically treating the biomass material with alkaline substances and / or oxides to obtain a matrix;
[0077] Laying an elastic film on at least one surface of the substrate to obtain a formed body;
[0078] The molded body is subjected to a pressurized curing treatment to obtain a softened composite material.
[0079] In some specific embodiments, the preparation method comprises the following steps:
[0080] Using the alkaline substance and / or the oxide to chemically treat the biomass material to obtain a matrix;
[0081] Laying the elastic film on one surface of the substrate to obtain a first formed body;
[0082] Applying an elastomer solution on the side of the substrate opposite to the elastic film, so that the elastomer material forms a film-like protective layer on the surface of the substrate to obtain a second molded body;
[0083] The second molded body is subjected to a pressurized curing process to obtain a softened composite material.
[0084] In the present invention, before the chemical treatment, a backing layer can be provided on the biomass material, so as to further fix and support the substrate. Specifically, the backing layer can be a non-woven fabric. Further, the backing layer can be assembled on one side of the biomass material, and then the chemical treatment is performed. Specifically, the backing layer can be assembled on one side of the biomass material using an adhesive. The present invention does not specifically limit the amount of the adhesive, and it can be selected as needed.
[0085] Furthermore, after the backing layer is assembled on one side of the biomass material, hot pressing can be performed to tightly combine the backing layer and the biomass material into one. Specifically, the hot pressing temperature can be 70-90°C, for example: 75°C, 80°C, 85°C, etc.; the hot pressing time can be 80-120 seconds, for example: 90 seconds, 100 seconds, 110 seconds, 120 seconds, etc.
[0086] The present invention does not specifically limit the adhesive, as long as the backing layer can be assembled on one side of the substrate, such as soy protein adhesive, polyurethane adhesive, hot melt adhesive, urea-formaldehyde resin and polyvinyl acetate emulsion mixed adhesive, or a combination of two or more thereof.
[0087] The present invention first uses alkaline substances and / or oxides to chemically treat biomass materials to obtain a matrix; the inventors of the present invention have found that by chemically treating biomass materials with alkaline substances, the rigid cellulose components can be swollen and softened, while removing part of the hemicellulose components. By chemically treating biomass materials with oxides, part of the hard lignin components in the substrate can be removed. Specifically, in the present invention, the time of the chemical treatment is preferably 1s-120h.
[0088] In the present invention, the biomass material may be chemically treated with an oxide first, and then with an alkaline substance. Alternatively, the biomass material may be chemically treated with an alkaline substance first, and then with an oxide.
[0089] In some specific embodiments, when an oxide is used to chemically treat a biomass material, the chemical treatment time is 5 h to 72 h, for example, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, 60 h, 65 h, 70 h, etc. When an alkaline substance is used to chemically treat a biomass material, the chemical treatment time is 1 s to 1 min, for example, 5 s, 10 s, 15 s, 20 s, 25 s, 30 s, 35 s, 40 s, 45 s, 50 s, 55 s, etc.
[0090] Further, when using oxides for preparation, an oxide solution can be prepared for chemical treatment. In the oxide solution, the mass fraction of the oxide is 0.5-5%, for example: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc. When using alkaline substances for preparation, an alkaline substance solution can be prepared for chemical treatment. In the alkaline substance solution, the mass fraction of the alkaline substance can be 10-30%, for example: 12%, 15%, 18%, 20%, 22%, 25%, 28%, etc.
[0091] Specifically, in the present invention, the alkaline substance includes one or a combination of two or more of KOH, NaOH, Na2SO3, K2SO3, Na2CO3, K2CO3; the oxide includes one or a combination of two or more of H2O2, NaClO2, NaClO.
[0092] In some specific embodiments, the elastic film is laid on one surface of the substrate to obtain a first molded body, and an elastomer solution is applied to the side of the substrate opposite to the elastic film so that the elastomer material forms a film-like protective layer on the surface of the substrate to obtain a second molded body.
[0093] Specifically, the solid content of the elastomer solution is 28-34%, for example: 29%, 30%, 31%, 32%, 33%, etc. The elastomer solution is applied to the side of the substrate opposite to the elastic film by one or a combination of two or more of paving, coating, casting and spraying to form a film-like protective layer, and at least part of the elastomer solution is infiltrated into the gaps and / or pores of the substrate, preferably by spraying.
[0094] The present invention does not specifically limit the amount of the elastomer solution used, and can be set as needed, as long as the function of the present invention can be achieved. Specifically, the amount of the elastomer solution used each time can be 50-100 g / m 2 , for example: 55g / m 2 , 60g / m 2 , 65g / m 2 , 70g / m 2 , 75g / m 2 , 80g / m 2 , 85g / m 2 , 90g / m 2 , 95g / m 2 wait.
[0095] The present invention does not impose any particular limitation on the number of spraying times, which can generally be 1 to 5 times.
[0096] Furthermore, the molded body or the second molded body is subjected to a pressurized curing treatment to obtain a softened composite material. The pressurized curing treatment can wrap the elastomer solution on the surface of the substrate to form a film-like protective layer, and at least a portion of the elastomer solution can penetrate into the gaps and / or pores of the substrate.
[0097] In some specific embodiments, the temperature of the pressurized curing is 60-90°C, for example: 65°C, 70°C, 75°C, 80°C, 85°C, etc.; the time of the pressurized curing is 5-10 minutes, for example: 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 7.5 minutes, 8 minutes, 8.5 minutes, 9 minutes, 9.5 minutes, etc.; the pressure of the pressurized curing is 1-4MPa, for example: 1.2MPa, 1.5MPa, 1.8MPa, 2MPa, 2.2MPa, 2.5MPa, 2.8MPa, 3MPa, 3.2MPa, 3.5MPa, 3.8MPa, etc.
[0098] Finally, the press-cured molded body or the second molded body may be polished to obtain the softened composite material of the present invention.
[0099] Example
[0100] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0101] The EVA film used is produced by Shengyuantai Plastic Business Department in Humen, Dongguan City, and has a thickness of 0.8mm.
[0102] The waterborne polyurethane is a waterborne polyurethane of model 1926 produced by Yoshida Chemical Co., Ltd. The waterborne polyurethane has a solid content of about 32%, a pH value of 6-8, and a viscosity of less than 350 mPa·s.
[0103] In the embodiment, the soy protein adhesive used is the soy protein adhesive produced by Zhejiang Lange New Material Technology Co., Ltd. The soy protein adhesive has a solid content of about 40%, a pH value of 6-8, and a viscosity of 1500-4000 cp(s).
[0104] Example 1
[0105] (1) Thin bamboo is used as the softening base material with a thickness of 0.15 mm.
[0106] (2) applying soybean protein adhesive to one side of the thin bamboo, and then performing hot pressing after non-woven fabric veneer, the hot pressing temperature is 90° C., and the hot pressing time is 120 seconds, to obtain a micro-thin bamboo material.
[0107] (3) The side of the micro-thin bamboo material that is not attached with the non-woven fabric is laminated with an EVA film, the EVA film is cut into the same size as the micro-thin bamboo, and the film is covered on the micro-thin bamboo with a thickness of 0.8 mm to obtain a molded body.
[0108] (4) The molded body is placed in a press for press curing at a temperature of 100° C., a time of 10 minutes, and a pressure of 4 MPa to obtain a cured product.
[0109] (5) The cured product is surface polished to obtain a softened composite material.
[0110] Example 2
[0111] (1) Thin bamboo is used as the softening base material with a thickness of 0.15 mm.
[0112] (2) applying soybean protein adhesive to one side of the thin bamboo, and then veneer with non-woven fabric, hot pressing at 90°C for 120 seconds to obtain a micro-thin bamboo material.
[0113] (3) preparing a sodium chlorite solution with a mass fraction of 2%, and immersing the thin bamboo material in the sodium chlorite solution for a treatment time of 24 hours to obtain a first chemical treatment product.
[0114] (4) The first chemical treatment product is washed with tap water until it becomes neutral and set aside.
[0115] (5) preparing a sodium hydroxide solution with a mass fraction of 20%, and immersing the first chemical treatment product in the sodium hydroxide solution for a treatment time of 5 seconds to obtain a second chemical treatment product.
[0116] (6) The second chemical treatment product is washed to neutrality and dried to obtain a dry product for later use.
[0117] (7) For the side of the dried product not attached with the non-woven fabric, the EVA film was cut into the same size as the thin bamboo, and the film was covered on the thin bamboo with a thickness of 0.8 mm to obtain a molded body.
[0118] (8) The molded body was placed in a press for pressurized curing at a temperature of 100° C., a time of 10 minutes, and a pressure of 4 MPa to obtain a cured product.
[0119] (9) The cured product is surface polished to obtain a softened composite material.
[0120] Example 3
[0121] (1) Thin bamboo is used as the softening base material with a thickness of 0.15 mm.
[0122] (2) applying soybean protein adhesive to one side of the thin bamboo, and then veneer with non-woven fabric, hot pressing at 90°C for 120 seconds to obtain a micro-thin bamboo material.
[0123] (3) preparing a sodium chlorite solution with a mass fraction of 2%, and immersing the thin bamboo material in the sodium chlorite solution for a treatment time of 24 hours to obtain a first chemical treatment product.
[0124] (4) The first chemical treatment product is washed with tap water until it becomes neutral and set aside.
[0125] (5) preparing a sodium hydroxide solution with a mass fraction of 20%, and immersing the first chemical treatment product in the sodium hydroxide solution for a treatment time of 5 seconds to obtain a second chemical treatment product.
[0126] (6) The second chemical treatment product is washed to neutrality and dried to obtain a dry product for later use.
[0127] (7) The aqueous polyurethane solution was sprayed on the side of the dried product that was attached to the nonwoven fabric three times to obtain a first molded body.
[0128] (8) The side of the first molded body not attached with the non-woven fabric is laminated with an EVA film, and the EVA film is cut into the same size as the thin bamboo, and the film is covered on the thin bamboo. The film thickness is 0.8 mm, and a second molded body is obtained.
[0129] (9) The second molded body was placed in a press for pressurized curing at a temperature of 100° C., a time of 10 minutes, and a pressure of 4 MPa to obtain a cured product.
[0130] (10) The cured product is surface polished.
[0131] Comparative Example 1
[0132] One side of the sliced thin bamboo was veneered with non-woven fabric, the adhesive used was soybean protein adhesive, the hot pressing temperature was 90°C, and the hot pressing time was 80 seconds. Finally, the thickness was 0.172mm, and the traditional thin bamboo material was obtained.
[0133] Performance Testing
[0134] 1. Tensile performance test
[0135] According to GB / T 12914-2018 "Constant tension method (20 mm / min) for the determination of tensile strength of paper and paperboard", the tensile properties of the softened composite material were tested. The sample of the specified size was stretched at a constant tensile speed (20 mm / min). The sample width was 15 mm ± 0.1 mm and the length was sufficient to be clamped between two clamps. The tensile strength and elongation at break were measured. The results are shown in Table 1.
[0136] 2. Folding resistance test
[0137] According to GB / T "Determination of folding resistance of paper and paperboard", the folding times and folding index (folding resistance) of the softened composite material were tested. The sample width was 15.0mm±0.1mm and the length was greater than 140mm. The MIT method was used for testing. The spring tension was adjusted to 9.81N. The folding head was fully swung 175 times±10 times per minute and the swing angle was 135°±2° with the vertical line. The results are shown in Table 1.
[0138] Table 1
[0139]
[0140] As can be seen from Table 1, the transverse tensile strength of Examples 1, 2, and 3 after softening treatment is significantly enhanced compared with the comparative example. Compared with Comparative Example 1, the longitudinal tensile strength of Examples 1, 2, and 3 is increased by 109.01%, 67.38%, and 78.11%, respectively, indicating that the EVA film composited on the surface of the micro-thin bamboo has a significant reinforcing effect. The elongation at break of the three embodiments is significantly improved compared with the comparative example, and the longitudinal direction is increased by 16.97%, 159.68%, and 76.54%, respectively, and the transverse direction is increased by 74.60%, 252.27%, and 333.31%, respectively. The increase in elongation at break indicates that the toughness of the material is enhanced, and it is less likely to break when stretched, indicating that the composite EVA film after softening treatment has a significant effect on improving the toughness of the embodiments.
[0141] The longitudinal and transverse folding times of the softened composite materials of Examples 1-3 are significantly improved compared with that of Comparative Example 1. The longitudinal folding times of Examples 1, 2, and 3 are increased by 32.20%, 3744.75%, and 2698.92% respectively after the softening treatment. Table 1 shows that the transverse folding times of Comparative Example 1 is 0, because the comparative example breaks during transverse bending and cannot complete an effective bending, while the transverse folding times of the softened examples can reach up to 9516 times. The folding resistance of Examples 1, 2, and 3 are increased by 3.71%, 52.05%, and 47.45% respectively compared with that of the comparative example, indicating that the folding resistance of thin bamboo is significantly improved after the softening treatment and then compounded with EVA film.
[0142] 2. Field emission electron microscope (SEM) test
[0143] The surface structure morphology and cross-sectional structure morphology of the softened composite materials of Examples 1-3 and the conventional composite material of Comparative Example 1 were observed by field emission electron microscopy (SEM). Figure 1 shown.
[0144] Depend on Figure 1 It can be seen that Figure 1 a is the cross-sectional structure of the traditional thin bamboo material of Comparative Example 1, Figure 1 The e is a magnified image of local cells of traditional thin bamboo materials. Figure 1 b, c, and d are the cross-sectional structural morphologies of Example 1, Example 2, and Example 3, respectively. Figure 1 f, g, and h are partial enlarged views of Example 1, Example 2, and Example 3. In the cross-sectional morphology of Examples 1-3, it can be seen that the EVA film and the substrate are composited and fused, among which Examples 2 and 3 have better composite effects with the substrate, and the gap between the EVA film and the substrate is reduced compared with Example 1. Figure 1It can be observed in fh that the EVA film melts during the hot pressing process and enters the gaps and / or pores of the substrate, wherein the bamboo cells in Examples 2 and 3 that have been chemically treated collapse to form a dense structure.
[0145] Figure 1 i, j, k, and l are the surface morphologies of comparative example 1, example 1, example 2, and example 3, respectively. It can be observed that the surfaces of examples 2 and 3 become rougher after treatment, which increases the contact area between the EVA film and the bamboo after melting, and makes the fusion with the bamboo cells tighter.
[0146] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0147] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A softened composite material, characterized in that: include: a substrate, the substrate being derived from a biomass material; as well as an elastic film, said elastic film being present on at least one surface of said substrate; and, At least a portion of the elastic film penetrates into the gaps and / or pores of the substrate.
2. The softened composite material according to claim 1, characterized in that: The matrix is obtained by chemically treating the biomass material; Preferably, the biomass material comprises wood material or bamboo material; and / or, The thickness of the biomass material is 0.1-1 mm, preferably 0.15-0.25 mm.
3. The softened composite material according to claim 1 or 2, characterized in that: The material of the elastic film includes ethylene-vinyl acetate copolymer; and / or, The thickness of the elastic film is 0.1-1.5 mm.
4. The softening composite material according to any one of claims 1 to 3, characterized in that: The elastic film exists on one surface of the substrate, and the substrate also contains an elastomeric material on the side opposite to the elastic film; wherein, The elastomeric material forms a film-like protective layer on the side of the substrate opposite to the elastic film; and at least a portion of the elastomeric material penetrates into the interstices and / or pores of the substrate; Preferably, the elastomeric material comprises waterborne polyurethane.
5. A method for preparing a flexible composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the steps of compositely molding an elastic film and a substrate, and allowing at least a portion of the elastic film to penetrate into the gaps and / or pores of the substrate.
6. The preparation method according to claim 5, characterized in that: The preparation method of the softened composite material comprises the following steps: Chemically treating the biomass material with alkaline substances and / or oxides to obtain a matrix; Laying an elastic film on at least one surface of the substrate to obtain a formed body; The molded body is subjected to a pressurized curing process to obtain a softened composite material.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: Using the alkaline substance and / or the oxide to chemically treat the biomass material to obtain a matrix; Laying the elastic film on one surface of the substrate to obtain a first formed body; Applying an elastomer solution on the side of the substrate opposite to the elastic film, so that the elastomer material forms a film-like protective layer on the surface of the substrate to obtain a second molded body; The second molded body is subjected to a pressurized curing process to obtain a softened composite material.
8. The preparation method according to claim 7, characterized in that: The alkaline substance includes one or a combination of two or more of KOH, NaOH, Na2SO3, K2SO3, Na2CO3, K2CO3; the oxide includes one or a combination of two or more of H2O2, NaClO2, NaClO; Preferably, the chemical treatment time is 1s-120h.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The solid content of the elastomer solution is 28-34%; and / or, The elastomer solution is applied to the side of the substrate opposite to the elastic film by one or a combination of two or more of laying, coating, casting and spraying to form a film-like protective layer.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The temperature of the pressurized curing is 60-90° C., the time of the pressurized curing is 5-10 minutes, and the pressure of the pressurized curing is 1-4 MPa.
Citation Information
Patent Citations
Flexible composite veneer and processing method thereof
CN103753656A
Production technology for bamboo wallpaper
CN104708681A
Preparation method for wood-bamboo reinforced resin composite material based on high-pressure densification
CN108772922A
Lightweight toughness laminated composite material
CN108790345A
EVA large hole composite foam material and preparation method
CN110229411A